The rights and duties of journalists in a constitutional democracy: An analytical exposition - Sambo, Abdul Fatai; Shuaib, Farid Sufian (INSI Publications, 2012)
Journalists, being the watchdog of the society, seem indispensable in a constitutional democracy. Yet, collision course between the journalists and the law enforcement agents appears unavoidable. Sometimes, journalists allege violence and intimidation on the part of the law enforcement agents. The law enforcement agents also allege that the journalists do not keep within their limits. In a constitutional democracy, certain rights and duties are expected of the journalists. This paper therefore analyses the rights and duties of journalists in this regard. To achieve this, it uses a number of international human rights instruments; constitutional provisions and case laws to make the legal analysis. It further discusses the independence of journalists and the protection of journalistic sources in a constitutional democracy. It finds that these rights are not adequately appreciated by many stakeholders and that the duties are sometimes neglected even by the journalists themselves. It further finds that these rights (together with its limitations) and duties are necessary in a constitutional democracy. Although the paper benefits countries practicing constitutional democracy, the focus is more on Malaysia.